Enculturation of Ambon’s Public Spaces as a Tool of Building Inclusivity of Segregated Communities - Sunarimahingsih, Yulita Titik; Yustina Trihoni Nalesti Dew; Heribertus Hermawan Pancasiwi; Octavianus Digdo Hartomo (European Journal of Social Science Education and Research, 2018)
Beside having significant values that would enrich the Indonesian nation, tribal, cultural, and religious diversity brought seeds of conflicts that could potentially disrupt social order and threaten national unity. The conflicts that occurred in Ambon from 1999 to 2004 were conflict examples that were caused by religious plurality that had appeared many societal problems that could not be fully resolved until today. The trust among Ambon’s plural communities had not returned well and it was even worsened by settlement segregation separating Muslim and Christian communities that factually brought potential for further conflicts. In the present life of Ambon’s segregated societ today public spaces inspired by brotherhood and “unity in diversity” spirits thatt could be meeting and socializing means of the communities and to reduce the social polarization were to be absolutely necessary. Unfortunately, the existing public spaces in Ambon for the time being served only as stages of activities and they did not connect with the communities’ social spectrums so that the public spaces remained meaningless. A public space here served just as a witness, not as a means of socializing in accordance with the communities’ cultures and characters. This paper would discuss how to integrate the communities’ cultures and characters into a public space design that had significant meaning in overcoming the polarization of Ambon’s segregated communities. The public space would be designed by taking into account a location choice where two segregated communities could easily meet. In the public space a macro space concept where the sea as the front page of Ambon communities should be applied and even forwarded since such a concept tended to be forgotten. Beside the spatial format, the public space should also be designed by facilitating various cultural-based activities so that the communities’ characteristics that were integrated in the urban culture and daily activities would appear in the public spaces.